Kinesio Taping® of the metacarpophalangeal joints and its effect on pain and hand function in individuals with rheumatoid arthritis - Sarah Roberts; Serela Ramklass; Robin Joubert (AOSIS, 2016)
Background: In persons suffering from rheumatoid arthritis (RA), the metacarpophalangeal (MCP) joints are commonly affected, resulting in inflammation, pain, joint instability, diminished grip strength and difficulties with function. However, the effectiveness of Kinesio Taping® of the MCP joints in alleviating the symptoms has not been established. Aim: To determine the effectiveness of bilateral Kinesio Taping® of the MCP joints on pain, range of motion, grip strength and hand function in elderly individuals previously diagnosed with RA. Methods: A repeated measure, experimental design was used over a 7-week period with the Kinesio Taping group (n = 30) receiving bilateral space correction Kinesio Taping® of the MCP joints with a joint protection (JP) group (n = 31) participating in JP workshops. The Kinesio Tape® was worn for 3 days a week with four applications during the data collection process. For the control group, 2-hour JP educational-behavioural workshops were run weekly for 4 weeks. Weekly assessments were completed for grip strength, ulnar deviation and pain (VAS), and two pre-intervention assessments and one post-intervention assessment was completed for the Michigan Hands Outcomes Questionnaire (MHQ). Results: Kinesio Taping® of the MCP joints showed a significant decrease in pain (p = 0.001) and improved range of motion (p = 0.001 bilaterally). JP was found to have a significant improvement in grip strength (p = 0.001 bilaterally) and in the work (p = 0.01) and activities of daily living (ADL) (p = 0.01) sections of the MHQ. No significant difference was found between groups after intervention in the majority of outcomes (p = 0.24) except for grip strength where a significant difference was found. Conclusion: Kinesio Taping® of the MCP joints is an effective conservative intervention to improve pain and MCP ulnar deviation in individuals with RA. Significance of the work: Kinesio Taping® of the MCP joints of individuals with RA showed a significant decrease in pain (p = 0.00) and improved range of motion (p = 0.001 bilaterally). JP was found to significantly improve grip strength (p = 0.001 bilaterally) and in the work (p = 0.01) and ADL (p = 0.01) sections of the MHQ. No significant difference was found between groups after intervention in the majority of outcomes (p = 0.24) except for grip strength where a significant difference was found (p = 0.001).